2022
DOI: 10.1111/ijfs.15582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isomalt on the quality of wheat flour dough and spicy wheat gluten sticks

Abstract: Summary The effects of different isomalt concentrations on the quality of wheat flour dough and spicy wheat gluten sticks (SWGS) were evaluated at the physical, structural and molecular levels. The results showed that the radial expansion rate (RER) and oil absorption rate (OAR) of SWGS increased first and then decreased with increased isomalt supplementation, which reached the maximum at 3 wt%. The pasting properties of wheat starch also changed, and the peak viscosity, breakdown and setback were decreased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…SEM analysis also further demonstrated that the protein molecules of LEP can enhance their binding to starch in wheat flour through hydrogen bonds. As a result, the surface of the LSGS became smoother, which was similar to previous research results [23].…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 90%
See 1 more Smart Citation
“…SEM analysis also further demonstrated that the protein molecules of LEP can enhance their binding to starch in wheat flour through hydrogen bonds. As a result, the surface of the LSGS became smoother, which was similar to previous research results [23].…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 90%
“…Referring to the method described by Jia et al, with some modifications [23], the texture properties of the samples before and after extrusion were studied by using a texture analyzer (TX-XT Plus, Beijing Oriental Anno Technology Co., Ltd., Beijing, China). The hardness and chewiness were determined in full texture mode using a cylindrical probe (P/75) with a diameter of 75 mm.…”
Section: Radical Expansion Rate (Rer) and Oil Absorption Rate (Oar)mentioning
confidence: 99%
“…As shown in Table 1, the water absorption of the dough increased significantly with the increase in gluten protein content. This is due to the high gluten protein content, which improves the water absorption of the dough through the interaction of hydrogen bonds with water molecules (Jia et al ., 2022). Gluten proteins absorb water and swell to form a network structure, thus improving the structure and physical properties of dough.…”
Section: Resultsmentioning
confidence: 99%